التعسف في استعمال الحق بين الزوجين في غانا: دراسة فقهية تحليلية - علي، عبد الرحمن (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study entitled “Abuse of the right between spouses: The case of Ghana” is an analytic jurisprudential study to explore the current situation of Ghanaian Muslims pertaining to the abuse of rights between spouses. As far as the research is concerned, there hasn't been any study on this topic before. The study is warranted because the frequency of abuse of spousal rights is high. The study is also considered to be complementary within the framework designed by the United nations which does not take into consideration the Islamic viewpoints and matters related to spousal rights. The study employs inductive analytical and empirical methods to examine the situation in Ghana on abuse of rights among Muslim married couples. In most cases, the abuse occurs due to circumstances relating to the system of patriarchy, maintenance and polygamy. Specifically, for women, their rights as wives are violated usually within the scope of maintenance and sexual obligation within polygamous marriages. This research hopes it would become a reference point for practitioners of legal and social institutions in resolving disputes between spouses in domestic abuse cases.